2011
DOI: 10.1089/brain.2011.0041
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Abnormality of Low to Moderately Organized White Matter in Schizophrenia

Abstract: Increasing evidence suggests that abnormal white matter is central to the pathophysiology and, potentially, the pathogenesis of schizophrenia (SCZ). The spatial distribution of observed abnormalities and the type of white matter involved remain to be elucidated. Seventeen chronically ill individuals with SCZ and 17 age-and gender-matched controls were studied using a 3T magnetic resonance imaging diffusion tensor imaging protocol designed to examine the abnormalities of white matter by region and by level of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Furthermore, age could not have confounded the finding of decreased FA in SZ compared to controls, which were well-matched age-wise, since co-varying for age in this situation would be expected to explain more of the error variance and thus further increase our power to detect a true group effect rather than decreasing it. Finally, although the SZ group contained a higher proportion of men than the control group, there is insufficient evidence to suspect that this would have artefactually created the well-replicated finding of decreased FA in SZ ( Ellison-Wright & Bullmore, 2009 ; Reading et al, 2011 ; Scheel et al, 2013 ; Schneiderman et al, 2011 ) and BD ( Vederine et al, 2011 ; Nortje et al, 2013 ; Lagopoulos et al, 2013 ). Although higher FA for men was found in the superior cerebellar peduncle, and for women in the corpus callosum ( Kanaan et al, 2014 ), there is also evidence ( Takao, Hayashi & Ohtomo, 2014 ) that after controlling for intracranial volume, sex differences seem to be due to differences in head size.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, age could not have confounded the finding of decreased FA in SZ compared to controls, which were well-matched age-wise, since co-varying for age in this situation would be expected to explain more of the error variance and thus further increase our power to detect a true group effect rather than decreasing it. Finally, although the SZ group contained a higher proportion of men than the control group, there is insufficient evidence to suspect that this would have artefactually created the well-replicated finding of decreased FA in SZ ( Ellison-Wright & Bullmore, 2009 ; Reading et al, 2011 ; Scheel et al, 2013 ; Schneiderman et al, 2011 ) and BD ( Vederine et al, 2011 ; Nortje et al, 2013 ; Lagopoulos et al, 2013 ). Although higher FA for men was found in the superior cerebellar peduncle, and for women in the corpus callosum ( Kanaan et al, 2014 ), there is also evidence ( Takao, Hayashi & Ohtomo, 2014 ) that after controlling for intracranial volume, sex differences seem to be due to differences in head size.…”
Section: Discussionmentioning
confidence: 99%
“…As opposed to tract specific differences, several studies have reported widespread diffusion abnormalities in all tested regions (Lim et al, 1999 ; Minami et al, 2003 ; Reading et al, 2011 ; Schneiderman et al, 2011 ; Knochel et al, 2012 ), though not all DTI studies report positive findings when examining differences between schizophrenia patients and healthy controls. Two early studies showed no anisotropy differences in small samples of schizophrenia patients (Steel et al, 2001 ; Foong et al, 2002 ).…”
Section: Diffusion Weighted Imaging Studiesmentioning
confidence: 99%
“…Scheel et al [33] found reduced fractional anisotropy values predominantly in frontal and temporal areas. Cui et al [41] found decreased fractional anisotropy in the left posterior corona radiata in CHSZ, whereas Reading et al [49] found that mean whole fractional anisotropy was decreased in CHSZ compared with normal controls, and Walther et al [51] found lower fractional anisotropy values in prefrontal and left temporal clusters. These findings suggest the variability among studies with respect to findings in CHSZ, with many white matter tracts seemingly affected, and difficulties in replicating findings (consistent with the conclusions of Melonakos et al [54]).…”
Section: Diffusion Tensor Imaging Studies In Chronic Schizophreniamentioning
confidence: 99%